Pengembangan Sistem Aplikasi Manajemen Proyek Berbasis Web (Studi Kasus: PT. Swadaya Graha) - Ardian Riftha Dhuha; Fajar Pradana; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Swadaya Graha (Semen Indonesia Group) is a company engaged in the manufacture and construction services. Based on the observation results of the company project report document can be concluded that the manajer proyek at PT. Swadaya Graha has the task to manage the project (project management). There are problems that occur in the current project management process, including the need for tools to facilitate the process of planning activities and project costs, tools to control the discrepancy between the plan and the realization of the project, tools that can reduce the number of report documents that must be filled, and can provide Project data in real-time. This study aims to develop a project management application system that can assist planning, project monitoring, real-time reporting data, and as an information tool for stakeholders. Built using a software development model called waterfall, the programming method used is object-oriented programming and embraces the concept of view controller model, besides the main method used in the project activity planning is the critical path method, aims to assist the process of project preparation and project scheduling . The results of the research indicate that at the testing stage there are 3 unit tests which resulted in conclusion that the functions are easy to understand, implemented and tested, 68 validation tests showing 68 functions to work properly, and compatibility tests showing the system can be used well on 8 type of web browser.